2022
DOI: 10.3390/antibiotics11010099
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Stewardship from Health Professionals’ Perspective: Awareness, Barriers, and Level of Implementation of the Program

Abstract: This study aimed to evaluate health professionals’ perceptions regarding the level of implementation of the Antimicrobials Stewardship (AMS) programs in Jordanian tertiary hospitals and to assess the perceived barriers to its implementation. During this cross-sectional study, a total of 157 healthcare providers agreed to participate (response rate 96.3%). Participants were asked to complete an electronic survey after meeting them at their working sites. Only 43.9% of the healthcare providers (n = 69) reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Eleven studies each identified the absence of leadership and minimal governmental support [ 27 , 28 , 35 42 ], and a lack of reliable laboratory infrastructure and microbiology laboratory support as challenges to effective ASP implementation [ 28 , 29 , 31 , 35 , 36 , 38 , 40 , 42 45 ]. Other identified barriers included inadequate orientation and training on ASP including rational antimicrobial use [ 27 , 30 , 36 , 41 , 44 , 46 ], prescribers’ negative attitudes to changes in antibiotic practices [ 27 , 30 , 33 , 35 , 37 , 43 , 47 ], and a lack of dedicated ASP funds [ 28 , 32 , 33 , 36 , 37 , 41 ]. Five studies each cited the absence of approved national guidelines or educational programs [ 27 , 36 , 43 , 45 , 48 ], and time constraints for prescribers [ 28 , 30 , 36 , 41 , 48 ] as barriers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies each identified the absence of leadership and minimal governmental support [ 27 , 28 , 35 42 ], and a lack of reliable laboratory infrastructure and microbiology laboratory support as challenges to effective ASP implementation [ 28 , 29 , 31 , 35 , 36 , 38 , 40 , 42 45 ]. Other identified barriers included inadequate orientation and training on ASP including rational antimicrobial use [ 27 , 30 , 36 , 41 , 44 , 46 ], prescribers’ negative attitudes to changes in antibiotic practices [ 27 , 30 , 33 , 35 , 37 , 43 , 47 ], and a lack of dedicated ASP funds [ 28 , 32 , 33 , 36 , 37 , 41 ]. Five studies each cited the absence of approved national guidelines or educational programs [ 27 , 36 , 43 , 45 , 48 ], and time constraints for prescribers [ 28 , 30 , 36 , 41 , 48 ] as barriers.…”
Section: Resultsmentioning
confidence: 99%
“…KAP) regarding ASP. Six of these studies (29%, 6/21) reported on all three elements: knowledge, attitude, and practice [ 27 , 45 , 47 , 50 – 52 ], and six others exclusively assessed ASP practice compliance [ 32 , 53 57 ]. The majority of the studies revealed that prescribers (physicians or pharmacists) had a sub-optimal knowledge of ASP and its basic principles [ 31 , 45 , 47 , 51 , 52 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, healthcare professionals perceived that electronic prescribing is beneficial and would reduce the high cost of prescribing antibiotics (i.e., reduce the expenditure of antibiotics), improve the efficacy and safety of antibiotic use, and may improve the ability to deliver AMS to optimise the rational use of antibiotics. In addition, many systematic reviews and studies demonstrated the impact of adopting the CDSS on antibiotics management and AMS [ 18 , 19 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, the need for a doctor’s prescription, a consultation with infection control teams, an accurate diagnosis of bacterial infections, and antibiotic sensitivity is essential [ 50 ]. It is encouraging to note that some of these steps are currently being implemented in the Arabian Peninsula [ 68 , 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%